1996
DOI: 10.1042/bj3150487
|View full text |Cite
|
Sign up to set email alerts
|

Compartment ablation analysis of the insulin-responsive glucose transporter (GLUT4) in 3T3-L1 adipocytes

Abstract: The translocation of a unique facilitative glucose transporter isoform (GLUT4) from an intracellular site to the plasma membrane accounts for the large insulin-dependent increase in glucose transport observed in muscle and adipose tissue. The intracellular location of GLUT4 in the basal state and the pathway by which it reaches the cell surface upon insulin stimulation are unclear. Here, we have examined the colocalization of GLUT4 with the transferrin receptor, a protein which is known to recycle through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
160
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(185 citation statements)
references
References 47 publications
25
160
0
Order By: Relevance
“…As shown in Figure 2, these compounds were effectively internalized in cells expressing GFP-Glut4. We, and others, have suggested that a significant proportion of intracellular Glut4 resides in a compartment spatially distinct from TfR in both adipocytes and muscle [1,5,15,30,39]. The only partial co-localization of GFPGlut4 or Glut4-GFP with Texas-Red transferrin (Figure 2) provides support for these observations and further suggests that the localization of the GFP-Glut4 chimaeras studied in the present work is accurately reflecting the localization of the Trafficking of green fluorescent protein-Glut4 in adipocytes…”
Section: Figure 2 Co-localization Of Gfp-glut4 With Texas Red Transfesupporting
confidence: 83%
See 1 more Smart Citation
“…As shown in Figure 2, these compounds were effectively internalized in cells expressing GFP-Glut4. We, and others, have suggested that a significant proportion of intracellular Glut4 resides in a compartment spatially distinct from TfR in both adipocytes and muscle [1,5,15,30,39]. The only partial co-localization of GFPGlut4 or Glut4-GFP with Texas-Red transferrin (Figure 2) provides support for these observations and further suggests that the localization of the GFP-Glut4 chimaeras studied in the present work is accurately reflecting the localization of the Trafficking of green fluorescent protein-Glut4 in adipocytes…”
Section: Figure 2 Co-localization Of Gfp-glut4 With Texas Red Transfesupporting
confidence: 83%
“…This recycling has been shown to involve, at least in part, clathrin-coated pits [12,13] via a dynamin\amphiphysin-dependent mechanism [14], and is consistent with the observed localization of Glut4 to clathrin lattices in the plasma membrane and the partial overlap of Glut4 with the transferrin receptor (TfR) itinerary [15][16][17]. After insulin withdrawal, Glut4 is rapidly internalized from the plasma membrane and is effectively sequestered within the cell until such time as insulin is re-introduced [18][19][20].…”
Section: Introductionsupporting
confidence: 76%
“…Insulin caused a substantial re-distribution of GFP-GLUT4, such that an almost continuous line of fluorescence was observed around the plasma membrane after 60 min (Figure 1b). Insulin did not cause a complete translocation of GLUT4, as would be expected from studies on the redistribution of native GLUT4 in these cells [3,4,6,18,19].…”
Section: Expression Of Gfp-glut4 In 3t3 L1 Adipocytesmentioning
confidence: 51%
“…Immunofluorescence and electron-microscopic analysis of non-stimulated cells has revealed that GLUT4-containing vesicles are clustered adjacent to early or late endosomes, in the trans-Golgi reticulum, or in the cytoplasm often close to the plasma membrane [1][2][3][4]. A small proportion of GLUT4 is also localized within the constitutively recycling endocytic system, but mounting evidence favours the existence of a unique pool of insulin-regulatable GLUT4 vesicles [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the "GLUT4 pathway" in insulin-sensitive cells is not completely understood. It has been shown, however, that internalized GLUT4 passes from early endosomes (31) to recycling endosomes (17,37,40) and then to specialized insulin-responsive storage vesicles, or IRVs, that represent the final target of insulin regulation (19,22,36). Transport of GLUT4 from early to recycling endosomes may proceed via a distinct population of vesicles that are marked by the presence of cellugyrin, which is absent from the IRVs (14, 15).…”
mentioning
confidence: 99%